The Role of Mothers' Parenting Attitudes and Child's Perceived Parenting Attitudes on Children's Emotion Recognition - Arzu ÇALIŞKAN SARI; Başak ŞAHİN-ACAR (Nesne Psikoloji Dergisi, 2018)
Parenting attitudes and children’s perception of parenting attitudes influence many different developmental skills of children, especially their social skills. The current study aims to examine the effects of mothers’ parenting attitudes and children’s perception of maternal parenting on children’s emotion recognition skills via the mediator role of children’s perception of parenting attitudes. One hundred and thirty 2nd-grade children and their mothers living in Ankara participated in the study. Kusche Emotion Inventory, Egna Minnen Beträffande Uppfostran Child form (sEMBU-C) were used as measurements for children while EMBU Parent form and a demographic form were used as measurements for mothers. Results showed that children whose mothers were high in emotional warmth got higher receptive emotion scores; while children, whose mothers scored higher in rejection, got lower receptive emotion scores. In addition, children’s perception of their mothers’ emotional warmth predicted the relationship between mother’s own emotional warmth and receptive emotion scores of children positively; while children’s perception of their mothers’ rejection predicted the relationship between mothers’ own rejection and children’s receptive emotion scores negatively. Overprotection had no predictive role in emotion understanding of children. Limitations of the current study and suggestions for future studies were discussed.